1992
DOI: 10.1227/00006123-199201000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graded Spinal Cord Injury on the Extrapyramidal and Pyramidal Motor Evoked Potentials of the Rat

Abstract: This study investigated the differential effects of graded spinal cord injury on the rat extrapyramidal motor evoked potential (exp-MEP) and pyramidal motor evoked potential (pyr-MEP) and the prognostic value of these effects in predicting postinjury motor performance in the rat model. In 20 rats subjected to graded spinal injury (10-100 g-cm), there was a differential injury threshold for ablation of exp-MEP and pyr-MEP. All peaks of the pyr-MEP were extinguished in the animals subjected to impact forces of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…13 If MEP monitoring is to be used to predict post-surgical motor function in rats, then MEP from the pyramidal rather than the extrapyramidal tract should be recorded, as previously emphasized. 18 Most published methods used to measure MEP are complex and require the use of various monitoring devices to guard against experimental error. These problems become major when the procedure is to be repeatedly applied to large numbers of animals, as might be required in transplantation experiments using rat SCI models.…”
Section: Discussionmentioning
confidence: 99%
“…13 If MEP monitoring is to be used to predict post-surgical motor function in rats, then MEP from the pyramidal rather than the extrapyramidal tract should be recorded, as previously emphasized. 18 Most published methods used to measure MEP are complex and require the use of various monitoring devices to guard against experimental error. These problems become major when the procedure is to be repeatedly applied to large numbers of animals, as might be required in transplantation experiments using rat SCI models.…”
Section: Discussionmentioning
confidence: 99%
“…Contusion injuries of the rat spinal cord, made by a weightdrop device with impact forces of 20-80 g-cm, also produce a decline of the amplitude of pyramidal and extrapyramidal MEPs with increasing impact forces (Shiau et al, 1992). Decreased MEP amplitudes were reported when ventral or lateral funiculi, but not when the dorsal funiculus were sectioned (Adamson et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…After graded spinal cord contusion, using a weight-drop device, several studies reported that the greatest locomotor recovery was observed in animals that received the lowest cord impact lesion (Basso et al, 1996;Magnuson et al, 1999;Metz et al, 2000;Raines recorded in animals that received mild or moderate spinal cord contusion but were abolished in animals with a severe contusion. The amplitude of MEPs decreased depending on the impact force (Baskin and Simpson 1987;Levy et al, 1986Levy et al, , 1987Shiau et al, 1992;Van de Meent et al, 1996). Similar results were observed after graded spinal cord clip compression (Fehlings et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Electrically induced MEPs have been used to evaluate the integrity of descending pathways in rodents under general anesthesia (Dull et al, 1990;Fehlings et al, 1988;Shiau et al, 1992;Stewart et al, 1990;Zappulla et al, 1988;Zileli and Schramm, 1991). We reported the use of transcranial magnetically induced MEPs in non-sedated rats (Cai et al, , 2005Fishback et al, 1995;Hadi et al, 2000;Linden et al, 1999) which were transmitted in the ventro-lateral funiculus of the spinal cord (Cai et al, , 2005Loy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These tests are frequently performed under anesthesia or sedation (Fehlings et al, 1988) which result in depression or distortion of the evoked response patterns (Chiba et al, 1998), causing changes suggestive of spinal cord injury (SCI) (Haghighi et al, 1996;Raines et al, 1988). Normative data (Fehlings et al, 1988) as well as data obtained following clinical and experimental SCI (Borgens et al, 2004;Raines et al, 1988) using electrically evoked stimulation have been characterized for SSEPs (Fehlings et al, 1988;Kaji and Sumner, 1987;Raines et al, 1988;Wojak et al, 1991), MEPs (Dull et al, 1990;Fehlings et al, 1988;Shiau et al, 1992;Stewart et al, 1990;Zappulla et al, 1988;Zileli and Schramm, 1991), and Hreflexes (Commissiong and Sauve, 1993;Mattson et al, 1984; 0165-0270/$ -see front matter © 2007 Elsevier B.V. All rights reserved. doi:10.1016/j.jneumeth.2007.05.021 Thompson et al, 1993Thompson et al, , 1998Thompson et al, , 2001Wirth et al, 2001) in humans and animals.…”
Section: Introductionmentioning
confidence: 99%